Environmental impact assessment on the example of modern innovative plant (Journal of Geography and Environmental Management, 2017)
also a technological breakthrough, aimed at preserving and improving the state of natural ecosystems. The names of the project – environmental impact assessment (EIA). This procedure became mandatory for existing and newly created objects of economic activity and is today an international standard. According to the draft EIA, at the design stage of any industrial or other object compulsorily conducted studies take the analysis of air masses, bodies of water, soil, a forecast of the future effects of exposure. The article deals with the project environmental impact assessment in the example of the innovative plant. The basis for EIA are the Environmental Code and «Instruction on carrying out impact assessment of planned economic and other activity on the environment in developing pre, pre project and project documentation», approved by the order № 204-p of the Minister of environmental protection of the Republic of Kazakhstan dated 28.06.2007. (With as 24.09.13g pr.№289 amended). During the environmental impact assessment have been identified potentially possible changes in the components of the implementation of the planned activities.